2020
DOI: 10.3390/ijms21061981
|View full text |Cite
|
Sign up to set email alerts
|

Maternal N-Acetyl Cysteine Intake Improved Glucose Tolerance in Obese Mice Offspring

Abstract: Exposure to certain environmental factors during the early stages of development was found to affect health in adulthood. Among other environmental factors, oxidative stress has been suggested to be involved in fetal programming, leading to elevated risk for metabolic disorders, including type 2 diabetes; however, the possibility that antioxidant consumption during early life may affect the development of diabetes has scarcely been studied. The aim of this study was to investigate the effects of N-acetyl-l-cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Of note, females were relatively resilient to HFD‐induced metabolic abnormalities, as has been shown before [24], independent of their stress response characteristics. Whereas the metabolic resiliency of female mice is presumably attributed to the protective effects of estrogen [25], testosterone levels might determine the differences between male Sub and Dom mice [26].…”
Section: Discussionsupporting
confidence: 58%
“…Of note, females were relatively resilient to HFD‐induced metabolic abnormalities, as has been shown before [24], independent of their stress response characteristics. Whereas the metabolic resiliency of female mice is presumably attributed to the protective effects of estrogen [25], testosterone levels might determine the differences between male Sub and Dom mice [26].…”
Section: Discussionsupporting
confidence: 58%
“…For five days from the moment the rats arrived in the animal research facility, they were fed granulated diet type LSM (Agropol, Motycz, Poland) of the following composition: 10.3% fats, 24.2% proteins, and 65.5% carbohydrates. After five days, the rats were divided into two equal groups as follows: Control group (C, n = 20): rats receiving standard LSM diet (Agropol, Motycz, Poland) containing 10.3% fats, 24.2% proteins, and 65.5% carbohydrates HFD group ( n = 20): a group of rats fed high-fat diet (Research Diet, USA, catalog number D12492) containing 59.8% fats, 20.1% proteins, and 20.1% carbohydrates [ 4 ] …”
Section: Methodsmentioning
confidence: 99%
“…HFD group ( n = 20): a group of rats fed high-fat diet (Research Diet, USA, catalog number D12492) containing 59.8% fats, 20.1% proteins, and 20.1% carbohydrates [ 4 ]…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is interesting to speculate that the enhancement of the P-eNOS level shown by NAC-treated animals could be a positive feature related to a possible preventive effect on insulin-resistant states. In accordance with NAC improvement of insulin sensitivity, Michlin et al [31] recently demonstrated that the maternal administration of NAC during pregnancy and lactation improves glucose tolerance of offspring at adulthood. Isolated islets of NAC-treated offspring (6 weeks old, before high fat diet feeding) had an increased efficacy of glucose-stimulated insulin secretion and a higher resistance to oxidative damage.…”
Section: Discussionmentioning
confidence: 77%